CORONA VIRUS DISEASE - 19 AND SOCIAL DISTANCE: A REVIEW STUDY (International Journal of Food and Nutritional Sciences, 2022)
Covid-19 is one of the infectious disease, it spreading world widly with lives peoples, There is no accurate medicine for covid-19, Co-vaccine, Covishield treatment developed primarily to control corona virus symptoms. This review article gives us to discuss about social distancing and tracing of cases. As per china report there are no positive cases in 309 cities.China having 34 cities have confirmed cases as on 13 april 2020. Covid-19 is a one of the infectious health problem, Covid-19 spread to person to person by the positive people of society. Covid-19 cases need to quarantine them and where they are contacted required to trace and identify the person to quarantine and followup is essential for 14 days. After that after that suggestion will be advice by health workers to continue self quarantine for 14 days. Highly careful is essential to find out in between positive cases and negatives cases. WHO designed and created partners in globally for specific field workers toimplement in many countries of the world. Developesmartphones are very helpfulto find the related cases in around us through the arogyasetu app. Daily and regular self report are necessary to track symptoms and signs covid-19. If there are found positive cases or indications of illness medical advice is important to take care and to control of severe condition. GPS location